Practical diagnostic testing for human immunodeficiency virus. - Jackson, J B (1988)
Since the discovery of human immunodeficiency virus (HIV) as the causative agent of acquired immunodeficiency syndrome in 1983, there has been a proliferation of diagnostic tests. These assays can be used to detect the presence of HIV antibody, HIV antigen, HIV ribonucleic and deoxyribonucleic acids, and HIV reverse transcriptase. Enzyme-linked immunosorbent assays, Western blot, radioimmunoprecipitation assays, indirect immunofluorescence assays, reverse transcriptase assays, and several molecular hybridization techniques are currently available. Enzyme-linked immunosorbent, Western blot, and indirect immunofluorescence assays for HIV antibody are very sensitive, specific, and adaptable to most laboratories. An enzyme-linked immunosorbent assay for HIV antigen is also readily adaptable to most laboratories and will be commercially available soon. While the other assays are more tedious, they are valuable confirmatory tests and are suitable for reference laboratories. The biohazards of performing HIV testing can be minimized with proper biosafety measures.